The Streptococcus pyogenes Capsule Is Required for Adhesion of Bacteria to Virus-Infected Alveolar Epithelial Cells and Lethal Bacterial-Viral Superinfection - Okamoto, Shigefumi (American Society for Microbiology, 2004)
An apparent worldwide resurgence of invasive group A Streptococcus (GAS) infections remains unexplained. However, we recently demonstrated in mice that when an otherwise nonlethal intranasal GAS infection is preceded by a nonlethal influenza A virus (IAV) infection, induction of lethal invasive GAS infections is often the result. In the present study, we established several isogenic mutants from a GAS isolate and evaluated several virulence factors as candidates responsible for the induction of invasive GAS infections. Disruption of the synthesis of the capsule, Mga, streptolysin O, streptolysin S, or streptococcal pyrogenic exotoxin B of GAS significantly reduced mortality among mice superinfected with IAV and a mutant. In addition, the number of GAS organisms adhering to IAV-infected alveolar epithelial cells was markedly reduced with the capsule-depleted mutant, although this was not the case with the other mutants. Wild-type GAS was found to bind directly to IAV particles, whereas the nonencapsulated mutant showed much less ability to bind. These results suggest that the capsule plays a key role in the invasion of host tissues by GAS following superinfection with IAV and GAS.